INVESTIGATING TEACHING MATERIALS IN AN EFL READING CLASSROOM - Stefany Gumayka; Sidik Indra Nugraha; Fauzi Miftakh (IKIP Siliwangi, 2024)
This research is aimed at investigating teaching materials development in an EFL reading classroom, specifically, it is focused on the factors need to be considered in preparing/developing reading materials, and students’ perception towards reading materials used by the teacher. This research used qualitative case study. The data were collected through interview from teacher and students, and documentation analysis using lesson plan. The site of this research is in one of Tangerang public school. And main participants are 1 English teacher and 3 students. The findings of this research showed that in preparing reading material the teacher involved several factors, including relevance to student live and interest, vocabulary level and complexity of the text, the use of technology and students’ feedback. The results of analysis on students’ perception on reading materials used by the teacher revealed that the students prefered reading material that has simplicity and imaginative content, enjoy reading material that have visual, value effective feedback mechanism, and acknowledge the role of reading material in English skill improvement. However, the students faced difficulties on reading material due the scientific language and text length.